2015
DOI: 10.2147/ijn.s75186
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)-block-poly(ε-caprolactone)– and phospholipid-based stealth nanoparticles with enhanced therapeutic efficacy on murine breast cancer by improved intracellular drug delivery

et al.

Abstract: Background Effective anticancer drug delivery to the tumor site without rapid body clearance is a prerequisite for successful chemotherapy. 1,2-distearoyl-sn-glycero-3-phospho-ethanolamine-N-(methoxy[polyethyleneglycol]-2000) (DSPE-PEG2000) has been widely used in the preparation of stealth liposomes. Although PEG chains can efficiently preserve liposomes from rapid clearance by the reticuloendothelial system (RES), its application has been hindered by poor cellular uptake and unsatisfactory thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…26 On the other hand, PEG-modified liposomes, like PTX–BSA-liposomes, have a hydration layer on the surface of the liposome, which results in inhibiting cellular uptake. 27,28 In the present study, confocal images clearly showed that DNSA–BSA-liposomes are taken up by AsPC-1 cells in the form of intact BSA-liposomes (Figure 4). In addition, the pretreatment of cytochalasin D (an inhibitor of micropinocytosis pathway) resulted in significant inhibition of the cellular uptake of Cy5-labeled BSA-liposomes by AsPC-1 cells but a filipin pretreatment (an inhibitor of the caveolae-mediated pathway) did not (Figure S5).…”
Section: Discussionsupporting
confidence: 65%
“…26 On the other hand, PEG-modified liposomes, like PTX–BSA-liposomes, have a hydration layer on the surface of the liposome, which results in inhibiting cellular uptake. 27,28 In the present study, confocal images clearly showed that DNSA–BSA-liposomes are taken up by AsPC-1 cells in the form of intact BSA-liposomes (Figure 4). In addition, the pretreatment of cytochalasin D (an inhibitor of micropinocytosis pathway) resulted in significant inhibition of the cellular uptake of Cy5-labeled BSA-liposomes by AsPC-1 cells but a filipin pretreatment (an inhibitor of the caveolae-mediated pathway) did not (Figure S5).…”
Section: Discussionsupporting
confidence: 65%
“…This might be due to the fact that the free PTX could be easily internalized by passive diffusion, whereas PTX in the NPs is gradually released into the cytoplasm and therefore the cytotoxicity is cumulative over time in vitro 48 - 50 . However, when applied in vivo , free PTX may cause serious side effect, whereas the targeted NPs would deliver PTX to the tumor site specifically 50 , 51 . Surprisingly, the IC50 was found to be consistent with the total uptake not only for 24 h but also for 48 h, where a lower IC50 matched a higher total uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Novel stealth nanoparticles of poly(ethylene glycol)-block-poly(ε-caprolactone)-and phospholipid-based were applied as PTX nanocarriers showing enhanced therapeutic effectiveness on murine breast cancer due to the improved intracellular drug delivery [ 301 ]. Additionally, PTX was encapsulated in novel lipid–polymer hybrid drug nanocarriers consisting of folate (FA) modified lipid-shell-1,2-distearoyl-sn-glycero-3-phosphoethanolamine- N -[methoxy (polyethylene glycol)-2000] DSPE-PEG2000 (as lipid-shell), and PCL-PEG-PCL (as self-assembled core) (FLPNPs) expressing controlled and targeted delivery of PTX inhibiting tumour growth [ 302 ].…”
Section: Types Of Nanocarriersmentioning
confidence: 99%